(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Identify some factors related to knowledge, attitude, and practice about prevention of injuries by sharp objects among nurses at Vinh Medical University Hospital in 2023. Research method: This study used a cross-sectional descriptive method with a sample size of 71 nurses who taking care for inpatients at Vinh Medical University Hospital from March to October 2023. Results: There was a statistically significant relationship between knowledge and age group, professional level, and number of times trained with p < 0.05. In addition, if knowledge was achieved, practice was 1,273 times higher than in the group of nurses with unsatisfactory knowledge (p < 0.05). Research results showed that there was a statistically significant relationship between practice and gender, work seniority, and number of times trained (p < 0.05). There was a positive relationship between nurses’ attitudes and practices on preventing occupational injuries caused by sharp objects with p < 0.05. Conclusion: Nurses need to update and fill gaps in knowledge about infection control in general and prevention of injuries by sharp objects in particular. In addition, it is necessary to properly and fully implement measures to prevent occupational injuries caused by sharp objects.